PENGUJIAN INDEKS GLIKEMIK DARI BERAS KESEHATAN - Nurjanah, Nunung; Soetrisno, Uken (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
STUDY ON GLYCEMIC INDEX OF RICE CLAIMED AS HEALTH-FOOD. Background: Daily consumption of high glycemic index foods, in long run can cause manifestation and development of diabetes, besides development of complication caused by diabetes. Now a days many kind of rice as health-foods are offered in the market. This rice are claimed to have many health benefits including managing diabetes due to low glycemic index. Objectives: There is still lack of information about GI on foods, so it is needed to study the value of GI. The information is important to the consumer and all health practitioners. Methods: The study used 3 kinds of rice that meant to lower blood glucose. GI was determined in vivo using 6 healthy women as subjects. Results: Results indicated that health food rice in the market has GI = 54 (Low GI) with relatively high in protein and fiber, while newly explored rice has Gla 68 dan 71 (moderate to high GI). Low GI rice no need to be added with common rice, and it is better not to polish the rice to keep flber content high and the GI value low. Keyword: glycemic index, health food, rice, diabetes, obesity, diet.